A multivariable definition of adequacy: Challenges and opportunities. (15th October 2013) - Brimblecombe, Simon
Abstract: The adoption of the International Labour Organization Recommendation concerning national floors of social protection, 2012 (No. 202) highlights the global importance of the extension of social security coverage. To maximize the positive impacts of coverage extension, not only should benefits and services be provided to the widest number of people and cover the greatest number of risks, but benefits have to be adequate. Whilst not without challenges, the level of coverage can be defined and measured. However, the definition of what is an adequate benefit is often less clear and has often relied on the use of one measure – the replacement ratio – to determine the relative adequacy of cash benefits. Given the multiple aims of social security systems, the use of a broader measure of adequacy that goes beyond cash benefit levels is not only more appropriate but necessary. In a context where financial constraints are arguably greater than ever, this article looks at the importance of adequacy and why such a broader consideration is required to measure the other aspects of benefit and service provision. It highlights how such a multivariable analysis could be constructed and the challenges of doing so. By attempting to measure if other goals of benefit provision are met – including quality of service, labour market aims, security of benefits and interaction with other stakeholders – the article seeks to contribute to widening the debate.